Research Advancements in Humanoid Compression Garments in Sports. (24th January 2013) - Fu, Weijie; Liu, Yu; Fang, Ying
The utilization of sport-related compression garments has attracted a great deal of attention from among Sports Science scholars. The function of the garments, such as to maintain muscle functions, reduce sports injuries and improve athletic performance, has been an issue of debate since the beginning of the new century. In this study, a number of methods including a literature review, logical analysis and mathematical statistics, are used to analyse earlier compression garments research, which can be found by searching hardcopy journals and online databases. Among the existing studies, most have tested and confirmed the functions of the garments; however, only a few have mentioned the underlying mechanism. Thus, by using more advanced and appropriate compression materials, future studies into compression garments will be focused on the vibration characteristics of muscles (soft tissues), and especially on their proprioceptive sensation, neuromuscular control, injury prevention and performance enhancement.